Making peace with Peach: Mexican female video gamers’ interpretations of female characters in video games - Treviño González, Raúl Alejandro (2024)
This article analyzes the interpretations of video game female characters residing in the metropolitan area of Monterrey, Mexico. A qualitative study was carried out from the perspective of cultural studies, for which fifteen players were interviewed about their tastes and opinions about female video game characters. It was found that most of the gamers hold critical positions towards sexualized female characters and that, in general, they accept and prefer female characters from Nintendo video games such as Mario Bros and Pokémon, franchises that gave them the first opportunities to play with feminine characters. On the other hand, it was found that mothers and other women in the family environment played an important role in the childhood of the interviewees, as mediators in their contact and love for video games. It is concluded that the consumption habits acquired by the players since childhood maintain a strong influence on their current consumption of video games.